Keputusan Investasi Dan Leverage Pada Nilai Perusahan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Mutiara Juliandari; Lidya Martha (Universitas Veteran Bangun Nusantara, 2023)
This study aims to examine the effect of investment decisions and leverage on the value of companies listed on the Indonesia Stock Exchange. The research population is all companies listed on the IDX for the 2017-2021 period. The sample was selected using the purposive sampling method with the sample criteria being companies listed on the IDX in the 2017-2021 period, which compared company values in the 2017-2021 period, and a sample of 57 companies was obtained. The data source is the company's annual financial report taken through the official website of the Indonesia Stock Exchange (www.idx.co.id). The testers used panel data regression analysis with the Eviews tool. Investment decisions are measured using the price earning ratio, while leverage is measured using the Debt to asset ratio and debt to equity ratio and company value is measured by price to book value. The results showed that the investment decision variable had a positive and significant effect on firm value, while leverage had a positive and significant effect on firm value.